Changes in Oral Anticoagulation Therapy over One Year in 51,000 Atrial Fibrillation Patients at Risk for Stroke: A Practice-Derived Study - Hohnloser, Stefan H.; Basic, Edin; Nabauer, Michael (Thrombosis and Haemostasis, 2019)
Background This study assessed changes in anticoagulation therapy over time in patients with atrial fibrillation (AF).Methods Analyses were performed on a claims-based dataset of 4 million health-insured individuals. The study population consisted of patients newly initiating a non-vitamin-K oral anticoagulants (NOACs) or vitamin K antagonist (VKA) for AF between 2013 and 2016. The study outcomes consisted of the proportion of patients who had (1) discontinued OAC treatment, (2) switched from VKA to NOAC, (3) switched from NOAC to VKA or (4) switched from one NOAC to another. Predictors of discontinuation or switching of OAC treatment were determined by Cox proportional hazards regression models with time-independent and time-dependent covariates.Results The study population comprised 51,606 AF patients initiating VKA (n = 21,468, 41.6%), apixaban (n = 8,832, 17.1%), dabigatran (n = 3,973, 7.7%) or rivaroxaban (n = 17,333, 33.6%). After 1 year, 29.9% of VKA and 29.5% of NOAC patients had discontinued OAC treatment without switching to another anticoagulant. A total of 10.7% of VKA patients switched to NOACs within 1 year, whereas 4.9% NOAC patients had switched to VKA. Of AF patients who were initiated on a NOAC, 5.2% switched to another NOAC. Treatment changes among NOAC starters were strongly associated with occurrence of stroke, myocardial infarction and gastrointestinal bleeding after treatment initiation. For VKA starters switching to a NOAC, stroke and bleeding events were associated with an increased likelihood of switching.Conclusion Overall discontinuation rates of VKA and NOACs are comparable over the first year of therapy, while switching from VKA to NOAC was more common than from NOAC to VKA. The majority of treatment changes were associated with clinical events.
Keywords: atrial fibrillation; non-vitamin-K oral anticoagulants; vitamin K antagonist; discontinuation; switching